Intellectual capital of technology-based incubators - M. Carolina Martins Rodrigues; Raul Pommer Barbosa; Luciana Aparecida Barbieri da Rosa; Maria José Sousa; Waleska Yone Yamakawa Zavatti Campos (Administrative Sciences, 2022)
The objective of this work is to evaluate the associations between the intellectual capital of technology-based incubators in the sustainability of incubated companies located in Portugal. For this purpose, the methodological strategy employed was the survey, and to test the hypotheses the Partial Least Squares Structural Equation Modeling PLS-SEM method was applied from a sample of 82 incubated company managers. The results show that the intellectual capital of the incubator company has a direct and positive relationship with the innovative capacity, satisfaction, and sustainability of the incubated company. In turn, the incubated company's innovative capacity has a direct and positive impact on sustainability itself. In addition, both the sustainability of the incubated company and its levels of satisfaction with the incubated company has a positive and direct impact on its competitive success. The management implications include the perception that the greater the effort to improve the human capital, structural capital, and relational capital of the incubated companies, the better will be the results achieved in supporting companies, helping start-ups develop sustainably and competitively in the market.
Keywords: 350; intellectual capital; success competitive and innovation; sustainability; technology-based incubators